Inclusive education and training of educators – legislation - de Carvalho, Aline dos Santos Moreira; Kaminski, Josilene Souza Conceição; Ribeiro Filho, Afonso Celso Sampaio; e Albuquerque, Shilton Matias Leal Tavares; Lima, Katia Samora; Borges, Tatiane de Sousa Soares (Seven Editora, 2023)
For some decades Inclusive Education has been developing in a secondary way, but in recent years it has become a relevant and pertinent theme in social and educational discussions. In this perspective, laws and decrees were sanctioned to guarantee the disabled as well as the gifted access to the same educational opportunities as other students. In this context, the present study aimed to specify the current legislation on Inclusive Education as well as the need for training of teachers who work in it, tracing a brief analysis and relationship between both. Scientific articles were selected that dealt with both the legislative theme and the training of teachers, both related to Inclusive education, using descriptors such as: legislation of Inclusive education and training of teachers for inclusive education. DOI:https://doi.org/10.56238/uniknowindevolp-031